Population-based estimates of age-specific cumulative risk of breast cancer for pathogenic variants in ATM - Anne-Laure Renault; James G. Dowty; Jason A. Steen; Shuai Li; Ingrid M. Winship; Graham G. Giles; John L. Hopper; Melissa C. Southey; Tú Nguyen-Dumont (Breast Cancer Research, 2022)
Abstract Background Multigene panel tests for breast cancer predisposition routinely include ATM as it is now a well-established breast cancer predisposition gene. Methods We included ATM in a multigene panel test applied to the Australian Breast Cancer Family Registry (ABCFR), a population-based case–control–family study of breast cancer, with the purpose of estimating the prevalence and penetrance of heterozygous ATM pathogenic variants from the family data, using segregation analysis. Results The estimated breast cancer hazard ratio for carriers of pathogenic ATM variants in the ABCFR was 1.32 (95% confidence interval 0.45–3.87; P = 0.6). The estimated cumulative risk of breast cancer to age 80 years for heterozygous ATM pathogenic variant carriers was estimated to be 13% (95% CI 4.6–30). Conclusions Although ATM has been definitively identified as a breast cancer predisposition gene, further evidence, such as variant-specific penetrance estimates, are needed to inform risk management strategies for carriers of pathogenic variants to increase the clinical utility of population testing of this gene.